Efficacy of Vaginal Prostaglandin E2 Versus Oxytocin for Induction of Labour in Patients with Premature Rupture of Membranes - Noor, Zainab; Liaqat, Shagufta; Khurshid, Misbah; Ali, Asif (Biological and Clinical Sciences Research Journal, 2025)
Prelabour rupture of membranes (PROM) at term is a common obstetric complication that necessitates timely labor induction to reduce maternal and neonatal morbidity. While both oxytocin and prostaglandin E2 (PGE2) are used for induction, their comparative efficacy remains under-investigated in low-resource settings such as Pakistan. Objective: To compare the efficacy of vaginal prostaglandin E2 versus intravenous oxytocin for labor induction in patients with term PROM in terms of timely vaginal delivery and reduction in cesarean rates. Methods: A randomized controlled trial was conducted over six months from April 2024 to September 2024 at the Department of Obstetrics & Gynaecology, Ibn-e-Siena Hospital, Multan. A total of 120 women with singleton term pregnancies (37–42 weeks) presenting with PROM of <6 hours duration were randomly assigned to receive either intravenous oxytocin (Group A, n = 60) or vaginal PGE2 (Group B, n = 60). Primary outcome was vaginal delivery within 24 hours. Secondary outcomes included induction-to-delivery interval, cesarean section rate, and failure of induction. Data were analyzed using SPSS version 23, with significance set at p ≤ 0.05. Results: Vaginal delivery within 24 hours was achieved in 73.3% of women in the PGE2 group versus 50.0% in the oxytocin group (p = 0.010). The mean induction-to-delivery interval was significantly shorter in the PGE2 group (7.2 ± 2.1 hours) compared to the oxytocin group (9.4 ± 2.3 hours; p < 0.001). Cesarean section rates were also significantly lower in the PGE2 group (20.0%) versus the oxytocin group (40.0%; p = 0.020). No serious adverse events were reported in either group. Conclusion: Vaginal PGE2 is more effective than intravenous oxytocin for labor induction in term PROM, with a higher likelihood of timely vaginal delivery and reduced cesarean risk. These findings support the inclusion of PGE2 in national labor induction guidelines, especially in high-volume, resource-limited healthcare settings in Pakistan.